Do you have a Latex Protocol? - Smith, Sue; Tyndall, Judi; Young, Alaine (Operating Room Nurses Association of Canada Journal, 1993)
In the November/December 1992 issue of the Canadian Operating Room Nursing Journal our submission titled “The Unsuspected Allergy” discussed the issue of a patient with latex allergy. This follow up document lists our hospital protocol, pro- vides a company product list and information on latex gloves and the employee.